2019
DOI: 10.3390/ma12223784
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi Method and Response Surface Methodology in the Treatment of Highly Contaminated Tannery Wastewater Using Commercial Potassium Ferrate

Abstract: The potential implementation of Envifer®, a commercial product containing potassium ferrate (40.1% K2FeO4), for the purification of highly contaminated tannery wastewater from leather dyeing processes was proposed. The employment of the Taguchi method for optimization of experiments allowed the discoloration (98.4%), chemical oxygen demand (77.2%), total organic carbon (75.7%), and suspended solids (96.9%) values to be lowered using 1.200 g/L K2FeO4 at pH 3 within 9 min. The application of the central composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 71 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…The optimization of application of potassium ferrate (VI) in the treatment of tannery wastewater have revealed R 2 and R adj. 2 values of 77.0% and 59.0% [ 55 ]. Furthermore, a Box–Behnken experimental design with RSM was used to optimize condition for microbial reduction on fresh-cut celery [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of application of potassium ferrate (VI) in the treatment of tannery wastewater have revealed R 2 and R adj. 2 values of 77.0% and 59.0% [ 55 ]. Furthermore, a Box–Behnken experimental design with RSM was used to optimize condition for microbial reduction on fresh-cut celery [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The adequacy and significance of the developed quadratic polynomial model for the sorption process were evaluated using the Fisher F-test and p-value of the analysis of variance ANOVA presented in Table 3. The goodness of fit was accessed by coefficient of determination R 2 which showed the variability in response predicted by the independent variables [59]. The R 2 , adjusted R 2 and predicted R 2 were found to be 0.9959, 0.9923, and 0.9547, respectively.…”
Section: Modeling Of Toc Removal By Rsmmentioning
confidence: 99%
“…In the case of the real sewage from the textile industry, R 2 and R 2 adj reached values of 0.8799 and 0.7999 [45]. In the case of using K 2 FeO 4 for the treatment of wastewater from the tanning industry other studies have reported R 2 and R 2 adj values of 0.77 and 0.59 [59] versus 0.95 and 0.74 in the case of employing K 2 FeO 4 for the treatment of synthetic sewage containing azo dye Anilan Blue GRL 250% [60]. A good fit between the empirical and approximated data was observed in the latter study.…”
Section: Ccd/rsm Findingsmentioning
confidence: 96%
“…Generally, greater efficiency of the oxidation of organic compounds can be observed, while conducting the oxidation process in an acidic environment, rather than in a neutral one [43,44]. Another study indicated that use of K 2 FeO 4 for the purification of highly polluted tannery wastewater from leather dyeing processes resulted in the discoloration (98.4% removal), chemical oxygen demand (77.2% removal), total organic carbon (75.7% removal), and suspended solids (96.9% removal); the reported values were the smallest when 1.200 g/L K 2 FeO 4 at pH 3 within 9 min was used [59]. On the other hand, the application of K 2 FeO 4 for the degradation of trichloroacetic acid and turbidity removal in synthetic water revealed that the highest efficiency achieved for trichloroacetic acid was 24%, while for turbidity the maximum removal efficiency was in the range of 85%-95%.…”
Section: Ccd/rsm Findingsmentioning
confidence: 99%